A critical analysis of children and young persons employment regulations enforcement in Malaysia. / Alliya Fuad Mohd Azri, Fatin Athira Mustapa and Izzat Arif Abdul Jamil - Mohd Azri, Alliya Fuad; Mustapa, Fatin Athira; Abdul Jamil, Izzat Arif (2014)
There are issues on the abuses of children and young persons in respect of employment in Malaysia. Children and young persons are distinct from one another. The main priority of this thesis is not only to analysis that distinction but also to find the loopholes within the Children and Young Persons (Employment) Act 1966 as well as its amendments in the Children and Young Persons (Employment) (Amendment) Act 2010. This research will compare laws on the employment of children and young persons in Malaysia in the Children and Young Persons (Employment) Act 1966, between the laws on children and young person employment in Singapore, as well as the laws in international conventions that Malaysia has ratified, namely the Convention on the Rights of the Child, the ILO's Minimum Age Convention (No. 138) (1973) and the Worst Forms of Child Labour Convention (No. 182) (1999). The issues regarding child labour shall be raised in this research paper. By determining the issues of child labour and the defects in Malaysian laws on child labour, recommendations shall be made to improving the Children and Young Persons (Employment) Act 1966 and its enforcement.